“El vent lluita per ésser flor”. La idea de la metamorfosi en la poesia de Joan Brossa i Federico García Lorca - Kurek, Marcin; Ziarkowska, Justyna (Studia Romanica Posnaniensia, 2021)
In the studies on poetry by Joan Brossa, his literary inspirations from the French tradition are indicated, but his connection with Spanish-language literature is almost nonexistent. The purpose of this article is to present Brossa’s testimonies about his Federico García Lorca readings and to compare his “Sonet del pur estrèpit” (1949) with Lorca’s “Muerte” (1931). Both poems show textual and conceptual similarities and share the theme of metamorphosis, so we propose their analysis to look for possible inspirations in different philosophical and aesthetic traditions (surrealism, Ovid, Darwin, Zen Buddhism).